USE OF PEATY ELIXIR ON SPRING RAPE AND POTATO SOWINGS FOR IMPROVEMENT OF PRODUCTION FERTILITY AND QUALITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
Our research target was to investigate how the Latvian-made humin substance for harvest and production quality can influence the seed-tuber pre-sowing treatment and the sprinkle of vegetative plants of spring rape and potatoes. Using the Peaty elixir under conditions of biologic farming f o r the pre-sowing treatment of spring rapeseeds provided a remarkable increase in the seed yield 0,19-0,31 t ha ‘. The crude intent within the seeds increased, on average, to 1,01-2,26%, and crude f a t to 1,57-1,88%. Treatment of the spring rape vegetative plants resulted the increase in the seed yield to 0,37 t ha ‘, increasing the crude fat content in the seeds to 1,45%>. The treatment of seed-tubers and vegetative potato plants provided a remarkable yield increase, and increased the starch content, decreasing nitrates in the production. Most effective the Peaty elixir, however, is when used together with mineral fertilizers.